HPLC-DAD analysis of Thymus serpyllum based natural pigments and investigation of their antimicrobial properties - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2014)
Purpose - In this study, it was aimed to investigate the antibacterial properties of natural pigments prepared from Thymus serpyllum. Design/methodology/approach - Al (III), Fe (II), Sn (II) and Cu (II) complexed natural pigments were obtained by using a precipitation method and the main constituents in the pigments were identified with HPLC-DAD. Also FTIR analysis was performed for further structural characterization. Moreover, the thermal stability and thermal degradation properties of the pigments were analyzed by thermogravimetric analyse (TGA). The antimicrobial activity of the thyme plant-extracted pigments was evaluated by measuring the minimal inhibitory concentration. Findings - Apigenin and luteolin flavones were detected as the main components of the natural dyes. Thermal degradation behaviour of the pigments was determined by means of TGA. All pigments showed high char yields and it was attributed to the high complexation between the metal and the ligand species. The antimicrobial activity of the thyme plant-extracted pigments was measured and it was found that all pigments had high antimicrobial activity. Aluminum-thymus pigments showed the highest antimicrobial efficiency among other pigments used in this study. Originality/value - The obtained pigments have high antimicrobial activities, and therefore, they can be used for the production of antimicrobial textiles. Furthermore, Thymus-based natural pigments might have potential applications in coating, paint, plastic industries, etc.
Keywords: Pigments; Antimicrobial; HPLC-DAD; HPLC-DAD; Minimal inhibition concentration; Thymus serpyllum; ESSENTIAL OILS; LIQUID-CHROMATOGRAPHY; IDENTIFICATION; FLAVONOIDS; DYE